Educational Competition Culture in South Korea: Impacts on Youth and Social Inequality - Chumnankul, Ponwipa (Thai Social Science Journal, 2026)
This article examines the culture of educational competition in South Korea, one of the highest-performing education systems in the world, which is also characterized by intense competition and significant pressure on students. The study aims to (1) analyze the nature of educational competition in South Korea, (2) investigate its impacts on youth, particularly in terms of mental health and quality of life, (3) explore the relationship between the education system and social inequality, and (4) propose policy recommendations to create a more balanced education system. The findings reveal that educational competition in South Korea is driven by high-stakes examinations, particularly the College Scholastic Ability Test (CSAT), and the widespread role of hagwon (private tutoring institutions). While these factors contribute to high academic performance, they also intensify social inequality. The study further finds that intense educational competition leads to significant negative impacts on youth, including stress, depression, and other mental health issues, as well as an imbalance between academic life and personal well-being. Moreover, the education system reinforces social inequality due to unequal access to educational resources, particularly among families with different socioeconomic backgrounds. The article suggests that education reform in South Korea should focus on reducing excessive competition, diversifying assessment systems, promoting youth mental health, and addressing educational inequality in order to build a more sustainable and equitable education system.